Hydrophobicity Enhances the Formation of Protein-Stabilized Foams - Roy J. B. M. Delahaije; Peter A. Wierenga (Molecules, 2022)
Screening proteins for their potential use in foam applications is very laborious and time consuming. It would be beneficial if the foam properties could be predicted based on their molecular properties, but this is currently not possible. For protein-stabilized emulsions, a model was recently introduced to predict the emulsion properties from the protein molecular properties. Since the fundamental mechanisms for foam and emulsion formation are very similar, it is of interest to determine whether the link to molecular properties defined in that model is also applicable to foams. This study aims to link the exposed hydrophobicity with the foam ability and foam stability, using lysozyme variants with altered hydrophobicity, obtained from controlled heat treatment (77 °C for 0–120 min). To establish this link, the molecular characteristics, interfacial properties, and foam ability and stability (at different concentrations) were analysed. The increasing hydrophobicity resulted in an increased adsorption rate constant, and for concentrations in the protein-poor regime, the increasing hydrophobicity enhanced foam ability (i.e., interfacial area created). At higher relative exposed hydrophobicity (i.e., ~2–5 times higher than native lysozyme), the adsorption rate constant and foam ability became independent of hydrophobicity. The foam stability (i.e., foam collapse) was affected by the initial foam structure. In the protein-rich regime—with nearly identical foam structure—the hydrophobicity did not affect the foam stability. The link between exposed hydrophobicity and foam ability confirms the similarity between protein-stabilized foams and emulsions, and thereby indicates that the model proposed for emulsions can be used to predict foam properties in the future.